ANALISIS PELAKSANAAN EVALUASI UNTUK MENINGKATKAN MUTU PEMBELAJARAN BIOLOGI DI SEKOLAH - Novi Indah Lestari; Abdul Razak; Lufri Lufri; Zulyusri Zulyusri (Program Studi Pendidikan Biologi Fakultas Ilmu Tarbiyah dan Keguruan Universitas Islam Negeri Raden Fatah Palembang, 2022)
In the learning process the teacher does not only transfer knowledge but must have academic qualifications in accordance with his field. Good learning planning is the key to achieving the expected learning objectives. The purpose of this study to analyze the implementation of the evaluation of Biology learning in schools. This research method is a meta-analysis by examining data sources originating from national or international journals published in the last five years (2017-2021). This research begins with formulating the topics to be studied and then formulating the problems. The next stage collecting relevant articles to collect data. The data was obtained from searching online journals through Google Scholar. The topic used are